Penerapan Kualifikasi Penyalahguna, Pecandu dan Korban Penyalahgunaan Tindak Pidana Narkotika demi Mewujudkan Nilai Keadilan - Dollar, Dollar; Riza, Khairul (Penerbit Goodwood, 2022)
Purpose: to determine the qualifications of abusers, addicts and victims of narcotics crime abuse, and to find out the application of the qualifications of abusers, addicts and victims of narcotics crime abuse in order to realize the value of justice. Method: used is normative juridical research through literature study with an approach to legislation and books. And also supported by empirical juridical research conducted through a series of field interviews with respondents and informants. Results: The research are the regulation of the qualifications of abusers, addicts and victims of narcotics crime abuse, which is regulated in Law Number 35 of 2009 concerning Narcotics and clarified by the Circular Letter of the Supreme Court of the Republic of Indonesia Number 4 of 2010, there is a clear difference and can be proven through a process. medical or testing of Narcotics users which shows whether there is a high dependence on Narcotics or vice versa. The application of qualifications for abusers, addicts and victims of narcotics crime abuse in order to realize the value of justice has not run optimally because there are still many perpetrators in narcotics crime cases, the qualifications are not distinguished between abusers, addicts and victims so that the imposition of imprisonment on anyone who becomes a defendant does not seem worth justice. Limitation: In addition, the application of qualifications for abusers, addicts and victims of narcotics crime is very necessary to provide a sense of justice in achieving legal goals, to provide appropriate punishments, to optimize law enforcement, and to be able to assist in the arrest of the main perpetrators so that the chain of narcotics circulation itself can be broken.